Effect of wheat and rice straw biochar produced at different temperatures on maize growth and nutrient dynamics of a calcareous soil. Issue 14 (6th December 2017) - Naeem, Muhammad Asif; Khalid, Muhammad; Aon, Muhammad; Abbas, Ghulam; Tahir, Muhammad; Amjad, Muhammad; Murtaza, Behzad; Yang, Aizheng; Akhtar, Saqib Saleem
ABSTRACT: The objective of this work was to study the effect of different biochar on alkaline calcareous soil, inherently low in soil organic carbon and fertility. Experiments were conducted in laboratory and greenhouse. Biochar was produced from wheat and rice straws at pyrolysis temperatures of 300°C, 400°C and 500°C (denoted as WSB300, WSB400, WSB500, RSB300, RSB400 and RSB500, respectively). In the first experiment, soil was incubated with biochar (1.0 % w/w) for up to 50 weeks. The results indicate that, WSB300 caused a significant decrease in soil pH and increased the CEC and nutrients (N, P and K) after 50 weeks of incubation. In the second experiment, maize plants were grown in pots containing calcareous soil amended with WSB and RSB for 60 days the results revealed that the application of WSB300 caused a significant increase in shoot (36%) and root (38%) dry matters over the respective control. Moreover, the highest nutrient concentrations (N and P) in shoot and root were observed with the WSB300 compared to other treatments. Therefore, it is concluded that application of wheat straw biochar produced at low temperature (WSB300) could be successfully used to improve soil properties and growth of plants in calcareous soils.